TA’ARUF DALAM KHITBAH SEBELUM PERKAWINAN - Badrudin (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2018)
This research is motivated by a number of candidates for the couple who did ta'aruf process in accordance with Islamic teachings. In addition there are the parents who tend to make economic factors and customs rather than religious factors. Khitbah In practice, there are customary rules that complicate the resulting tercegahnya perkawinan.Tujuan this research is to get information from Al-Qur'an how the concept ta'aruf and Khitbah accordance with the teachings of Islam. The method in this research is patterned library research (library research), by collecting, reading, and studying the books that are related to this discussion. Primary sources in the form of the Qur'an and Tafseer related to the concept ta'aruf and Khitbah..Berdasarkan results of research by the author that ta'aruf concepts in the Qur'an intention is to know each other's personality, social background, culture, education , family, and religion. The khitbah in the Qur'an, it is done after the prospective spouses already feel a lack of compatibility with ta'aruf process. Khitbah (making a proposal) can be conveyed by innuendo or by clear expression. The proposal is submitted to the widow satire that is still in the prescribed period. While the proposal with overt expressions conveyed to a widow who runs the prescribed period and to the virgin. Ta'aruf and khitbah in the Qur'an recommends to prioritize aspects of religion than any other factor. Because the only religion who will be able to preserve the marriage. While property, birth, status, beauty, good looks will fade and one day will be lost. Rules regarding ta'aruf Qur'an and Khitbah not allow seclusion (alone).